Ion-cyclotron absorption of fast waves in a cylindrical current-carrying plasma - Grishanov, N.I.; Azarenkov, N.A. (Вопросы атомной науки и техники, 2021)
Influence of a longitudinal stationary current on the absorption and the radial structure of fast waves in a cylindrical current-carrying plasma is discussed. To evaluate the dispersion equation for fast waves, there was used the dielectric tensor taking into account the radial current structure and geometry of the confining helical magnetic field by the plasma safety factor. It is shown that the damping rate of fast waves in a non-equilibrium current-carrying plasma differ from those for an equilibrium plasma column in a homogeneous magnetic field nearby the cutoffs and resonances due to the rotational transformation (including shear-effects) of the helical magnetic field lines.